Symbiosis of chemotherapy and aggressive cancer surgery in improving the results of treatment for locally advanced cancer of the cervix uteri - G. A. Khakimov; D. M. Iskhakov; Sh. G. Khakimova; G. G. Khakimova (ABV-press, 2016)
By arming gynecologic oncology with current chemotherapy regimens and aggressive cancer surgery elements, we can have larger numbers of cured patients with locally advanced cancer of the cervix uteri, by improving the early and late results of treatment.